Agenda Setting Media dalam Acara“President’s Corner” di MetroTV - Sonjaya, Soni; Handayanti, Asih; Surachman, Akhmad Yani (PRoListik : Jurnal Ilmu Komunikasi, 2024)
The popular press offers a framework for direct explanation of social and political reality based on individual and personal actions and reactions. The fragmentation and shallowing of complex social reality, according to him, tends to weaken the audience's ability to understand events, and to think and act rationally. The "President's Corner" program has political content ahead of the 2019 Election. The broadcast of this program only presents positive qualities. The diversion of social issues through imagery from the life side of the "President's Corner" in this event looks very strong. The media's agenda setting is directed towards support for Joko Widodo during the 2019 election. The media's partiality towards the political interests of a group is too visible in this event. The connection between MetroTV and President's Corner was responded to as a pro, this was seen as an element of media neutrality in this program. The framing element in this event is very visible, especially when the media presents a positive image of Joko Widodo through adjectives.